Pengaruh Sertifikasi Terhadap Profesionalisme Guru Pada Era PendidikanModern di UPT SDN II Sidokumpul - Novia Nur Safitri; Sri Minarti (CV. ITTC INDONESIA, 2026)
Teacher certification is an official process for recognizing teacher competency according to government standards as an effort to improve the quality of education. This study aims to analyze the role of certification in enhancing teacher professionalism, particularly at the elementary school level in the modern education era. The results indicate that certification has a positive impact on increasing teacher self-confidence, motivation, discipline, and performance in the learning process. Furthermore, certification also contributes to improving the welfare, dignity, and protection of the teaching profession. However, the effectiveness of certification in improving professionalism is not absolute, as it is influenced by other factors such as competence, motivation, experience, and support from the school environment. Furthermore, certified teachers still face various challenges, such as limited technological capabilities, high administrative burdens, and lack of access to advanced training. Therefore, certification needs to be balanced with continuous competency development so that it is not merely an administrative requirement but also optimally improves the quality of learning.